IMPLEMENTASI MANAJEMEN SYARIAH PADA BIMBINGAN MANASIK HAJI DAN UMRAH DI TRAVEL SELATOUR CABANG BUKITTINGGI - Hidayat, Abil Rahmad; Madalis, Muhammad; Harfandi, Harfandi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2023)
This research is based on the travel agency Travel Selatour Bukittinggi branch which has received permission from (Kemenang), Sharia Management in managing the Hajj and Umrah Manasik Guidance, as well as the number of pilgrims departing at Travel Selatour Bukittinggi branch. The research method used is a qualitative method in the form of a descriptive method regarding analyzing the potential of sharia management in the guidance of Hajj and Umrah rituals at Travel Selatour Bukittinggi branch. The data collection technique is an interview with the manager of Travel Selatour Bukittinggi branch. From the results of research conducted on the guidance of Hajj and Umrah rituals at the Bukittinggi branch of Selatour Travel, the implementation of Sharia Management, namely Sidik, Amanah, Tablig and Fatanah.